Annual Research Review: Cross‐cultural similarities and differences in parenting. (11th November 2021) - Lansford, Jennifer E.
Abstract : This article reviews contemporary research on cross‐cultural similarities and differences in parenting. The article begins by providing a definition of culture and how both parenting and culture can change over historical time. The article then presents some classic theoretical frameworks for understanding culture and parenting before considering why parenting may be similar across cultures and why parenting may be different across cultures. The article next turns to a review of cross‐cultural similarities and differences in several aspects of parenting, including physical caregiving, cognitive stimulation, warmth and acceptance, control and monitoring, and discipline. Cultural normativeness and beliefs on the legitimacy of parental authority are then considered as potential moderators that contribute to cross‐cultural similarities and differences in relations between parenting and child outcomes. The article then considers implications for parenting interventions and laws and policies related to parenting. Finally, the article suggests directions for future research.